Current challenges in toxicological research: Evaluation of the developmental toxicity of manufactured nanomaterials - Isabella Fernandes Delgado; Francisco JosÃ© Roma Paumgartten (Fundação Oswaldo Cruz (FIOCRUZ), 2013)
Nanomaterials are particles or fibers with at least one of the three dimensions in the size range between 1 and 100 nm. Owing to unique physical and chemical properties, nano-sized particles (NPs) have a variety of industrial uses and are more and more prevalent in everyday life. However, despite the growing number of nanotechnology products, health risk assessment of NPs is in its early infancy. The potential adverse effects of NPs on prenatal development are even less well investigated. This article summarizes the literature on the developmental toxicity of NPs. Generally, the studies are very recent and include ex vivo experiments using non-mammalian species, in vitro assays (mouse embryonic stem cell test) and in vivo investigations using rodents. Very little has been published on the effects of NPs on the development and function of the human placenta or on the transference of NPs into the human embryo and fetus. Some limitations of using ex vivo and in vitro assays to predict adverse effects of NPs on human prenatal development are discussed in this overview. The structural and functional differences between the rodent and human placenta in early pregnancy and their possible relevance to the transplacental passage of NPs are also commented upon.